2015
DOI: 10.1159/000437443
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Percutaneous Ultrasound-Guided Kidney Biopsy in Patients with AA Amyloidosis

Abstract: Background: Bleeding is the most frequent complication of kidney biopsy. Although bleeding risk in patients with AA amyloidosis after kidney biopsy has not been studied in a large population, AA amyloidosis has long been perceived as a risk factor for bleeding. The aim of the present study was to evaluate post-biopsy bleeding risk in patients with AA amyloidosis. Methods: We retrospectively analyzed bleeding complications in 88 patients with AA amyloidosis and 202 controls after percutaneous kidney biopsy. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…A review of complications of percutaneous renal biopsy from three teaching hospitals in the UK over a 25-year period showed that the bleeding risk was no higher among amyloidosis patients than those with other pathologies [10]. Similar findings were reported in a study of 101 amyloidosis patients at the Mayo Clinic [11] as well as a more recent study of 88 patients with systemic AA amyloidosis [12]. In the largest study evaluating the safety of endomyocardial biopsy in cardiac amyloidosis, 4 complications occurred after 73 procedures, resulting in a complication rate of approximately 5.5% [13], which is similar to that reported for endomyocardial biopsy in general patient cohorts [14].…”
Section: Biopsy Of a Clinically Involved Organsupporting
confidence: 63%
“…A review of complications of percutaneous renal biopsy from three teaching hospitals in the UK over a 25-year period showed that the bleeding risk was no higher among amyloidosis patients than those with other pathologies [10]. Similar findings were reported in a study of 101 amyloidosis patients at the Mayo Clinic [11] as well as a more recent study of 88 patients with systemic AA amyloidosis [12]. In the largest study evaluating the safety of endomyocardial biopsy in cardiac amyloidosis, 4 complications occurred after 73 procedures, resulting in a complication rate of approximately 5.5% [13], which is similar to that reported for endomyocardial biopsy in general patient cohorts [14].…”
Section: Biopsy Of a Clinically Involved Organsupporting
confidence: 63%
“…To overcome this obstacle hindering earlier diagnosis and more efficient treatment of CKD 4–8 , it is imperative to develop a better understanding of the structure of the renal microvasculature highly correlated with the pathogenesis underlying CKD 9, 10 . However, certain concerns regarding the procedure for diagnosing CKD including: (1) the pathophysiology-based abnormal microvasculature remains to be refined; (2) conventional pathological diagnosis depends mainly on 2D structures, but 3D imaging is recommended to profile the abnormal areas from the pathology perspective, including the fine lesions in the kidney 11, 12 ; and (3) there is a risk of bleeding, infection or other complications in patients after undergoing renal biopsy 1315 ; need to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of renal amyloid is established by biopsy of the kidney [22]. Bleeding is a significant complication of biopsy due to amyloid involvement of the vasculature and abnormalities of hemostasis related to amyloidosis.…”
Section: An Overview Of Amyloidosismentioning
confidence: 99%